EVALUASI KAPASITAS DAN KEBIJAKAN INVENTORI GUDANG KOMPONEN AKSESORIS NATIONAL VEHICLE DISTRIBUTION CENTER SUNTER DI PT TOYOTA ASTRA MOTOR DENGAN METODE KANBAN - Veren
PT Toyota Astra Motor is responsible for the distribution process of Toyota cars and accessories installation. National Vehicle Distribution Center (NVDC) is used to be an area for the installation process and there is 3 location of NVDC, and the research, the focus is located at NVDC Sunter. The process of installing vehicle accessories involves a warehouse that operates using the supplier kanban metod. The application of the supplier kanban method in the warehouse has not been optimal and causing several types of accessory components has a high inventory level. Especially for 4 types of accessory components whose inventory count exceeds the shelf capacity during period September 2019 to February 2020. This research will evaluate the number of kanban accessories components in the NVDC Sunter warehouse using the Kanban optimization method with a discrete-event simulation (Yousefi et al., 2012). The performance criteria reviewed in this research are service level and total kanban. There are 4 scenarios to generate the best solution, 2 scenarios using a single objective function and 2 scenarios using multiple objective with the hierarchical optimization method. Based on this solution, the storage capacity of accessory components in the warehouse will also be evaluated. The best solution is generated by the hierarchical optimization method with the objective function priority is to maximize the service level value with a total kanban value of 338 kanban and a percentage of improvement from the actual condition of 32.4%. The number of kanban for P5162-BZA07 type components is 75, P5023-BZA01 is 102, P5281-BZA0K is 94, and P5625-BZA27 is 67.Based on the standard for the number of new kanban, an evaluation of the storage space for accessory components is carried out in the warehouse. The evaluation result show that the storage space for the study accessory components needs to be increased by about 16.29 square meters because they cannot accommodate all the stored inventory.